Study on the morphological and optical properties of porous anodic alumina - Chin, Ing khang (2016)
Porous anodic alumina (PAA) has been investigated extensively over the last few decades due to its effectiveness and simplicity to grow self-ordered nanopores, which is excellent as a template for nanostructures fabrication. To introduce more feasibilities in anodizing PAA, the attempt to fabricate highly ordered PAA should be done at room temperature without cooling system. Besides, a more cost effective material should be investigated to be used as a counter electrode. In this project, works are focused on the investigation of fabrication and characterizations of PAA under various anodizing parameters, including anodizing voltage, type of aluminum substrate, concentration of electrolyte and type of counter electrode. It was found that the surface morphological aspects of PAA are significantly dependent on the anodizing parameters that have been investigated. The pore size is linearly dependent on the anodizing voltage from 20 to 40 V, varying in the range of 30 to 50 nm. However at 50 V, after pore widening process, the PAA is fractured into fibrous structure. The effect of different types of aluminum substrates on anodization was also demonstrated.